See You Someday Soon - Miller, Pat Zietlow; Lee, Suzy, 1974- (New York : Roaring Brook Press, 2022)
A child imagines ways to connect with their grandmother who lives far way.
new kids book 2022 summer.
Ages 3-6.
Grades K-1.
Keywords: Grandmothers -- Fiction; Grandparent and child -- Fiction; Picture books